PERSPEKTIF HUKUM KELUARGA DAN HARTA BENDA PERKAWINAN TERHADAP ASAS NASIONALITAS DALAM KEPEMILIKAN HARTA BERSAMA DALAM PERKAWINAN CAMPURAN - Nabila Ratu Utami (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This study aims to examine the application of the nationality principle in joint property ownership within mixed marriages in Indonesia and to analyze the legal implications of the Constitutional Court Decision No. 69/PUU-XIII/2015 on the legal certainty of land ownership rights for Indonesian citizens (WNI). The nationality principle, as stipulated in the Basic Agrarian Law (UUPA), restricts ownership of Freehold Title (Hak Milik) and Building Use Rights (HGB) exclusively to Indonesian citizens. In mixed marriages, the absence of a prenuptial agreement results in joint property ownership, which may cause Indonesians to lose land ownership rights as the property is deemed jointly owned with a foreign spouse, as exemplified in the case of Mrs. Ike Farida. The Constitutional Court Decision No. 69/PUU-XIII/2015 marks a significant legal milestone by allowing the creation of prenuptial agreements, including property separation agreements, even after marriage. This ruling strengthens constitutional protection and legal certainty for Indonesians to safeguard their land rights. However, its implementation still faces administrative barriers, limited public awareness, and a lack of understanding regarding the importance of marital agreements. Therefore, collaboration among the government, legal institutions, and society is essential to enhance the effectiveness of this ruling in ensuring legal certainty and protecting the rights of Indonesian citizens. Keyword: Principle of Nationality, Joint Property, Mixed Marriage, Marital Agreement Abstrak: Penelitian ini bertujuan mengkaji penerapan asas nasionalitas dalam kepemilikan harta bersama pada perkawinan campuran di Indonesia serta menganalisis implikasi yuridis Putusan Mahkamah Konstitusi (MK) Nomor 69/PUU-XIII/2015 terhadap kepastian hukum hak kepemilikan tanah bagi Warga Negara Indonesia (WNI). Asas nasionalitas dalam Undang-Undang Pokok Agraria (UUPA) membatasi kepemilikan Hak Milik (HM) dan Hak Guna Bangunan (HGB) hanya bagi WNI. Dalam perkawinan campuran, ketiadaan perjanjian kawin menyebabkan terbentuknya harta bersama, yang berpotensi membuat WNI kehilangan hak atas tanah karena dianggap dimiliki bersama dengan pasangan Warga Negara Asing (WNA), sebagaimana terjadi pada kasus Ny. Ike Farida. Putusan MK No. 69/PUU-XIII/2015 menjadi tonggak penting karena memperbolehkan pembuatan perjanjian kawin, termasuk pemisahan harta, setelah perkawinan berlangsung. Putusan ini memperkuat perlindungan konstitusional bagi WNI dalam mempertahankan hak atas tanahnya. Namun, implementasinya masih terkendala oleh faktor administratif, minimnya sosialisasi, serta kurangnya pemahaman masyarakat mengenai pentingnya perjanjian kawin. Oleh karena itu, dibutuhkan kolaborasi pemerintah, lembaga hukum, dan masyarakat untuk meningkatkan efektivitas penerapan putusan ini guna menjamin kepastian hukum dan perlindungan hak WNI. Kata kunci: Asas Nasionalitas, Harta Bersama, Perkawinan Campuran, Perjanjian Kawin